2019
DOI: 10.1167/19.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Visual temporal integration windows are adult-like in 5- to 7-year-old children

Abstract: The visual system must organize dynamic input into useful percepts across time, balancing between stability and sensitivity to change. The temporal integration window (TIW) has been hypothesized to underlie this balance: If two or more stimuli fall within the same TIW, they are integrated into a single percept; those that fall in different windows are segmented (Arnett & Di Lollo, 1979; Wutz, Muschter, van Koningsbruggen, Weisz, & Melcher, 2016). Visual TIWs have been studied in adults, showing average windows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…It could therefore also be the case that this temporal window is widened, due to greater uncertainty about when they are executing a saccade. If children are unable to segregate stimulus information into pre- or postsaccadic categories, they would not be able to accurately calculate intrasaccadic position changes; however, we think that this explanation is less likely, as a number of studies suggest that temporal integration windows in children do not differ from adults ( Arnett & di Lollo, 1979 ; Hogben, Rodino, Clark, & Pratt, 1995 ) and, more importantly, that children are also able to segment temporal information as well as adults by the age of 5 ( Freschl, Melcher, Kaldy, & Blaser, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…It could therefore also be the case that this temporal window is widened, due to greater uncertainty about when they are executing a saccade. If children are unable to segregate stimulus information into pre- or postsaccadic categories, they would not be able to accurately calculate intrasaccadic position changes; however, we think that this explanation is less likely, as a number of studies suggest that temporal integration windows in children do not differ from adults ( Arnett & di Lollo, 1979 ; Hogben, Rodino, Clark, & Pratt, 1995 ) and, more importantly, that children are also able to segment temporal information as well as adults by the age of 5 ( Freschl, Melcher, Kaldy, & Blaser, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…Integration and segmentation occur at many levels throughout the brain, from flicker fusion in the retina [Gorea, 2015; Kalloniatis & Luu, 2007], which reaches adult levels in early infancy [Hartmann & Banks, 1992], to episodic memory in the medial temporal structures [Nyberg, McIntosh, Houle, Nilsson, & Tulving, 1996], which is still maturing into late childhood [Ghetti & Bunge, 2012]. In this study, we target mid‐level vision processes involved in parsing input into meaningful patterns and forms [Freschl, Melcher, Kaldy, & Blaser, 2019; Wutz & Melcher, 2014; Wutz, Muschter, van Koningsbruggen, Weisz, & Melcher, 2016]; those processes parse the fractionated, dynamic images of a flipbook into a coherent story.…”
Section: Introductionmentioning
confidence: 99%
“…In typical development, it has been shown that 6‐ to 15‐month‐old infants have lower visual temporal resolution (relatively poor segmentation) as compared to adults [Farzin, Rivera, & Whitney, 2011a], with segmentation thresholds around 1000–2000 ms in infants (6‐ and 15‐month‐olds, respectively) and 100 ms in adults – suggesting infants are more tuned to integrate visual information across time. Then, by around 5 years of age, temporal processing reaches adult levels, suggesting a finer tuning toward perceiving rapid change across time [Arnett & Di Lollo, 1979; Freschl et al, 2019; Hogben, Rodino, Clark, & Pratt, 1995]. Any differences in temporal processing may perturb perceptual and cognitive processes that rely on well‐adapted timing, such as object individuation [Drewes, Zhu, Wutz, & Melcher, 2015; Wutz & Melcher, 2014], multisensory integration [Wallace & Stevenson, 2014], visual working memory [Wutz & Melcher, 2013, 2014], apparent motion [Fairhall, Albi, & Melcher, 2014], motion perception [Milne, Swettenham, & Campbell, 2005], face processing [Evers, Steyaert, Noens, & Wagemans, 2015; Uljarevic & Hamilton, 2013], action sequence perception, and action planning [Faivre & Koch, 2014], potentially influencing social skills such as turn‐taking in joint tasks or in conversation [Schirmer, Meck, & Penney, 2016; Trevarthen & Daniel, 2005]; differences that could contribute to developmental trajectories in autism spectrum disorder (ASD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Operationally speaking, this is defined as “the maximal delay between two events for which a response differs from the summed responses associated with each event” ( Faivre and Koch, 2014b ). Note that this definition is different from other usages of “temporal integration window” in the literature; for example, some use it to refer to the brain’s temporal “resolution” ( Arnett and Di Lollo, 1979 ; Blake and Lee, 2005 ; Wutz et al, 2016 ), a topic that has been the focus of recent clinical ( Stevenson et al, 2014 ; Zhou et al, 2018 ) and developmental research ( Freschl et al, 2019 ; Ronconi et al, 2020 ) and is related to hypotheses about whether consciousness is continuous or discrete (for a review, see Herzog et al, 2020 ).…”
Section: Windows Of Integrationmentioning
confidence: 99%